Eksperimentasi Pembelajaran Matematika DenganMetode Numbered Head Together (NHT) Dan Quiz TeamDitinjau Dari Kemampuan Awal Siswa Kelas VII Di SMPNegeri 1 Surakarta Semester Genap Tahun Ajaran 2016/2017 - Purbasari, Hariatmi, Rita Pramujiyanti Khotimah, S.Si, M.Sc (2017)
The research aim to test and analyze : (1) the influence of learning methods of Numbered Head Together (NHT) and Quiz Team in mathematics achievement. (2) the effect of the initial ability of students in mathematics achievement. (3) the effect of the interaction between the learning method and the initial ability of students in mathematics achievement. The research was conducted at SMP Negeri 1 Surakarta in VII Grade of even semester of academic year 2016/2017 with the population of 256 students. Samples from this research are two classes which totaled 64 students. VII G class as an experimental class using learning methods of Numbered Head Together (NHT). VII H class as a control class using learning methods of Quiz Team. The data collection use test and documentation. Data were analyzed using two-way analysis of variance with different cells. The results of the data analysis with a significance level of 5% was concluded that (1) there is no effect of learning methods of Numbered Head Together (NHT) and Quiz Team in mathematics achievement. (2) there is the effect of the initial ability of students in mathematics achievement. (3) there is no interaction between the learning method of Numbered Head Together (NHT) and Quiz Team in terms of initial ability of students in mathematics achievement.